Reaching to a rewarded visual stimulus: interhemispheric conflict and hand use in monkeys with forebrain commissurotomy. - Eacott, M; Gaffan, D (1989)
Monkeys (Macaca fascicularis) learned simultaneous visual discriminations for food reward. Two coloured patterns were presented one above the other and the monkey chose one by touching it with a hand. On some trials, conflicting information was presented to the two visual hemifields. For example, in the left hemifield the stimulus associated with reward was in the higher position and in the right hemifield the stimulus associated with reward was in the lower position. On some of these conflict trials the monkeys were required to use the left hand and on others the right. Normal monkeys, monkeys with section of the anterior commissure and the posterior corpus callosum, and monkeys with section of the anterior commissure and the whole of the corpus callosum performed this task. Our aim was to test the hypothesis that following forebrain commissurotomy, the response made by each hand would be predominantly influenced by the visual information put into the hemisphere contralateral to that hand. If this is true then choices in the conflict test should vary systematically with hand use. This hypothesis was not confirmed. We conclude that when a monkey reaches to a rewarded visual stimulus, information about the reward history of the stimulus is integrated between the hemispheres before influencing the motor control of the hand that reaches, either by a peripheral or a subcortical route.